EKSISTENSI TRADISI LARANGAN ADAT DESA GOLAN DAN MIRAH SEBAGAI IDENTITAS MASYARAKAT DI KABUPATEN PONOROGO - Yessi Kumala Dewi; Arief Sudrajat (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2023)
Tradition is a habit of people in an area that has been passed down from generation to generation by our ancestors for a long time. One form of tradition that develops in the community is an oral tradition, for example, the tradition of customary prohibitions in Ponorogo Regency. This study aims to find out about the existence of the customary prohibition tradition found in the Golan and Mirah villages, given that these villages have customary prohibitions not to unite in any case, including marriage and other activities involving the Golan and Mirah village groups. In order to approach the problem, an anthropolinguistic approach is used as references. The data were collected through interviews and literature studies which were analyzed descriptively qualitatively. The results of this study indicate that there are 5 swearing utterances by Ki Honggolono: 1) Golan and Mirah residents are prohibited from marrying; 2) goods originating from the Golan village are prohibited from being brought to Mirah, and vice versa; 3) goods originating from the two villages are prohibited from being collected or combined; 4) the people of Mirah are prohibited from planting and are not allowed to make products related to soybeans; and 5) Golan residents are prohibited from using straw as roofing material for houses. It is disastrous if anyone violates these rules. This tradition can be interpreted as a form of identity for a community group. Until now, the tradition of customary prohibition is still maintained and maintained in the midst of globalization.